French Culinary Term Categorization in Essential of Professional Cooking’s Book - Khaeril Sungkawa; Toni Ari Wibowo (Tourism Department, State Polytechnic of Banyuwangi, 2024)
The book entitled essentials of professional cooking is a book that is very suitable to be used as a reference for culinary lovers, cooks or especially for beginners in cooking, but, dishes originating from western countries generally use French term. French cooking terms are still widely found in western cookbooks, the fact is that every region has cooking terms according to the language they use, where these terms are used for communication when working in the kitchen. Cooking terms in French have become well-known in every food and beverage industry, it's no wonder that beginners or students often encounter cooking terms in French when working in the kitchen or reading western cookbooks. This research was conducted on a book entitled Essentials of Professional Cooking by Wayne Gisslen about categories of cooking terms in French and their meanings in English. The writer conducts this research by using descriptive method, this study is designed to get information concerning with the meaning of culinary term of French in essential professional cooking’s book and its category. In the end, the writer conducted in finding Culinary Categorization also literal meaning of French culinary term that found some forms such as Word, Compound word and Collocation also in meaning based on culinary world by using cookery encyclopedia and French-English dictionary.